Dual-functional imprinted magnetic nanoprobes for fluorescence detection of N-nitrosodiphenylamine. Issue 20 (14th May 2018) - Hu, Yufeng; Liu, Jie; Li, Junyu; Chen, Tao; Wu, Minghuo
Abstract : Fluorescent magnetic molecularly imprinted nanoprobes were developed for the detection of N -nitrosodiphenylamine. Abstract : Fluorescent magnetic molecularly imprinted polymers (FMMIPs) were prepared in a one-pot sol–gel polymerization process using Mn-doped ZnS quantum dots (QDs) as a fluorescent core, N -nitrosodiphenylamine (NDPhA) as a template, (3-aminopropyl) triethoxysilane (APTES) as a functional monomer, and tetraethylorthosilicate (TEOS) as a cross-linker. These FMMIPs could be used for sensing NDPhA based on their fluorescence quenching. The fluorescence intensity of the FMMIPs decreased as the concentration of NDPhA increased in the range of 0–120 μM, with a detection limit of 0.69 μM. The FMMIPs exhibited selectivity towards NDPhA over their structural analogs N -nitrosodiethylamine and sulfanilamide. Finally, the FMMIPs were successfully applied to detect NDPhA in tap water and seawater samples, and the average recoveries of NDPhA at different spiking levels ranged from 93.1% to 105.2% with relative standard deviations below 8.4%. This work provides a simple fabrication method for fluorescent magnetic MIP sensors, which can be used for the rapid determination and separation of nitrosamines from complex matrices.